Experimental investigation on the bond behaviour of steel reinforcement in self-healing concrete. (20th June 2023) - Hermawan, Harry; Wiktor, Virginie; Gruyaert, Elke; Serna, Pedro
Highlights: The addition of healing agents to the concrete improves the bond strength of rebar. Longitudinal cracking decreases the bond strength between steel rebar and concrete. The autonomous self-healing effect promotes a slight bond strength recovery. Crack closure is evident by the inclusion of healing agents. Abstract: The appearance of cracks in structural reinforced concrete is inevitable and when out of control, it can be the cause of concrete failure. The ingress of water and harmful substances via the cracks is critical as the embedded steel reinforcements in the concrete can be corroded. Crack formation will directly weaken the bond between the reinforcing bar and concrete. To mitigate this issue, cracks should be repaired and closed relatively fast and this can potentially be obtained by incorporating self-healing technologies. Self-healing concrete demonstrates a good healing efficiency by the use of smart materials which allow for autonomous healing or enhance the autogenous healing mechanism of concrete. However, it is questioned whether the precipitates only artificially close the crack or also contribute to improve the bond with the reinforcement. In this study, an experimental investigation was conducted to evaluate the bond properties of self-healing concrete by means of pull-out tests. Four types of healing agents were used including two non-axenic biomass agents (HTN and YEAST) and two commercial agents (crystalline admixture and bacteria (CA and BAC)). The fresh properties and mechanical properties of the concrete including the healing agents were initially investigated. Pull-out tests were executed on uncracked, cracked and healed specimens. Two healing periods (28 and 112 days water immersion) were considered to evaluate the effect of healing time on bond recovery. Test results confirm that the addition of healing agents induced a better improvement of bond properties of steel reinforcement in uncracked concretes with respect to the reference concrete (no healing agent added). The highest bond strength enhancement by 57% on uncracked concrete was obtained with the addition of CA, while the inclusion of other agents such BAC, HTN and YEAST also possessed the bond strength improvement by 47, 21 and 7%, respectively. The presence of a longitudinal crack in concrete significantly reduced the bond strength up to 80% and this effect was not significantly affected by the crack size, when considering cracks in the range of 200─500 µm, and the introduction of healing agents. Nevertheless, the bond properties were slightly recovered after healing due to self-healing effects and formation of healing products in the crack was clearly visible.